CRAN-20. THE TEN-YEAR EVOLUTIONARY TRAJECTORY OF A HIGHLY RECURRENT PAEDIATRIC HIGH GRADE NEUROEPITHELIAL TUMOUR WITH MN1:BEND2 FUSION. Issue 2 (22nd June 2018) - Burford, Anna; Mackay, Alan; Popov, Sergey; Vinci, Maria; Carvalho, Diana; Clarke, Matthew; Izquierdo, Elisa; Avery, Aimee; Jacques, Thomas S; Ingram, Wendy J; Moore, Andrew S; Frawley, Kieran; et al.
Abstract: Astroblastomas are rare brain tumours which predominate in children and young adults, and have a controversial claim as a distinct entity, with no established WHO grade. Reports suggest a better outcome than high grade gliomas, though they frequently recur. Recently, they have been described to overlap with a newly-discovered group of tumours described as 'high grade neuroepithelial tumour with MN1 alteration' (CNS HGNET-MN1), defined by global methylation patterns and strongly associated with gene fusions targeting MN1 . We have studied a rare case of astroblastoma arising in a 6 year-old girl, with multiple recurrences over a period of 10 years, with the pathognomonic MN1:BEND2 fusion. Exome sequencing of eleven surgical interventions allowed for a phylogenetic reconstruction of tumour evolution, which when integrated with clinical, pathological and radiological data provide for a detailed understanding of disease progression, with initial treatment driving tumour dissemination along four distinct trajectories. Infiltration of distant sites was associated with gains of chromosomal arms and later genome doubling. There was evidence of convergent evolution of different lesions acquiring distinct alterations targeting the NF-kB pathway, supported by strong immunohistochemical staining of RELA, and high levels of target gene expression, such as IL8. These data represent an unique opportunity to understand the evolutionary history of a highly recurrent childhood brain tumour, and provide novel therapeutic targets for astroblastoma / CNS HGNET-MN1.